EFEKTIVITAS PGPB (Plant Growth Promoting Bacteria) DARI AKAR TUMBUHAN PUTRI MALU (Mimosa pudica) TERHADAP KANDUNGAN KLOROFIL DAN STOMATA CABAI RAWIT (Capsicum frutescens) - Liwutang, Rifani Ch; Yalindua, Aser; Posumah, Danny Ch (LPPM Politeknik Saint Paul Sorong, 2024)
Rifani Chatrin Liwutang. 18 502 003. Effectiveness of PGPB (Plant Growth Promoting Bacteria) from the roots of the Putri Malu (Mimosa pudica) plant on the chlorophyll content and stomata of cayenne pepper (Capsicum frutescens). Thesis. Biology Study Program, Faculty of Mathematics, Natural and Earth Sciences, Manado State University in Tondano. 2024. Dr. Aser Yalindua, MP as supervisor I and Danny Christian Posumah, S.Si, M.Si as supervisor II. Cayenne pepper (Capsicum frutescens) is one of the vegetable commodities that people really need as an ingredient to add flavor to food. Problems often faced by chili farmers include the availability of fertilizer and the presence of pest plants for cultivated plants which affect plant productivity. The aim of this research is to determine the effect of giving PGPB (Plant Growth Promoting Bacteria) from the roots of the putrimalu plant on the chlorophyll content and stomata of cayenne pepper leaves. This research was carried out at the Biology Department Laboratory, FMIPAK, Manado State University. This research used a Completely Randomized Design with five PGPB treatments, namely; P0= Control, P1= 10 ml, P2= 20 ml, P3=30 ml and P4=40 ml in three replications. The data was analyzed using Oneway Anova and continued with the Post Hoc LSD (Least Significant Difference) test at a confidence level of 95%. The results of this research show that PGPB treatment can increase plant growth such as plant height, number of leaves and root volume.